Penggunaan Kain Marmer pada Exotic Dramatic Style - Faizanisa Ulaya; Mirda Aryadi; Dinni Yanuarmi; Desra Imelda (INDO PUBLISHING, 2026)
This project report aims to examine the use of marble fabric as the main material in designing fashion garments with an Exotic Dramatic style. Marble fabric is an exploratory textile material created through the utilization of textile waste that is shredded and combined using adhesive materials, resulting in unique textures, patterns, and visual characteristics. The artistic appearance, rich texture, and exclusive impression of marble fabric are considered suitable for the characteristics of the Exotic Dramatic style, which emphasizes exotic, unique, and dramatic elements. The method used in this creative work consists of the stages of planning, exploration, design, realization, and evaluation. The design process began with the exploration of marble fabric materials, followed by the analysis of design elements and principles, concept development, fashion design creation, and the realization of fashion products. The work assessment was conducted to analyze the suitability between the characteristics of marble fabric and the application of the Exotic Dramatic style, including aspects of form, texture, color, silhouette, and aesthetic value. In addition, the assessment aimed to identify the potential of marble fabric as an alternative material capable of enhancing creativity and innovation in fashion design. The resulting works consist of three levels of fashion products: ready-to-wear (Velvet Eclipse), ready-to-wear Deluxe (Ethnic Motion), and Haute couture (Ethnic Allure). These three creations demonstrate that the use of marble fabric can strengthen the exotic and dramatic character of fashion garments while producing artistic, unique, and visually appealing designs. The presentation of the collection is carried out by showcasing the completed works to the public through a fashion show, supported by various elements such as stage design, lighting, music, and makeup.